[Translated article] Lateral extra-articular tenodesis in association to all-inside anterior cruciate ligament reconstruction does not modify return to play in basketball players: A comparative cohort study - E. García-Albó; J. Nomdedéu Sancho; M. Gispert Estadella; R. Sevil Mayayo; J.V. Andrés-Peiró; J. Pijoan Bueno; M.M. Reverté-Vinaixa; J. Minguell-Monyart (Revista Española de Cirugía Ortopédica y Traumatología, 2025)
Introduction: Return to play rates after anterior cruciate ligament (ACL) reconstruction range between 50-98% depending on sport professionality, without being modified by the addition of an extra-articular augmentation (EA). The objective of the study is to describe the rate of return to play in our cohort. The hypothesis is that the addition of EA increases that rate. Material and methods: A retrospective, descriptive and analytical study of a 130 basketball players cohort between 18 and 45 years old, whom underwent ACL reconstruction between the years 2018 and 2022, with a minimum follow-up of 18 months. Data was collected by reviewing medical records. IKDC score was registered after one year from surgery. All patients operated from 2020 received an extra-articular tenodesis. Results: Of all patients, 72.31% returned to training, 70.77% returned to competition and 46.15%returned to the same level of performance prior to injury. The EA group (46.15%) did not increase the rate of return to competition (P = .552) nor to the same level of performance (P = .664). The mean IKDC. score was 86.83 (SD 14.85), and was not higher in the EA group (P = .418). However, its value was higher in the players who returned to training, competition and level of performance(P < .05). EA did not delay the return to play in any group (P = .282). Conclusion: To sum up, the EA does not modify the return to sport rate. Higher IKDC values predict a greater return to sport rate in all groups. Prospective studies with larger sample size and longer follow-up time are required. Resumen: Introducción: Las tasas de vuelta al deporte tras la reconstrucción del ligamento cruzado anterior (LCA) oscilan entre un 50-98% en función de la profesionalidad, sin verse modificadas de forma significativa por la adición de una aumentación extraarticular (AE), pero sí disminuye las rerroturas. El objetivo del estudio es describir la tasa de vuelta al deporte en nuestra cohorte y demostrar que la AE no la modifica. Material y métodos: Estudio retrospectivo, descriptivo y analítico de una cohorte de 130 jugadores de baloncesto federado entre 18 y 45 años, intervenidos entre 2018 y 2022, con seguimiento mínimo de 18 meses. Los datos fueron obtenidos mediante revisión de historias clínica y registro del IKDC al año. A partir de 2020, a todos se les añadió una tenodesis extraarticular. Resultados: Un 72,31% volvió a los entrenamientos, un 70,77% a jugar partido oficial y un 46,15% al mismo rendimiento previo a la lesión. La AE (46,15%) no aumentó la tasa de vuelta a partidos (p = 0,552) ni al mismo rendimiento (p = 0,664). El IKDC medio fue de 86,83 (DE: 14,85) y no fue mayor en el grupo de AE (p = 0,418), en cambio, el valor sí fue mayor en los jugadores que volvieron a los entrenamientos, partidos y rendimiento (p < 0,05). La AE no retrasó la vuelta al deporte en ningún grupo (p = 0,282). Conclusiones: La AE no modifica la tasa de vuelta al deporte en nuestro estudio. Valores mayores del IKDC sí predicen un mayor retorno al deporte. Estudios con mayor tamaño muestral, prospectivos y de más tiempo de seguimiento son necesarios.